Salt of dysprosium(iii) tetrakis(hexafluoroacetylacetonate) with 1,1′-dimethyl-4,4′-bipyridinium as a new single-ion magnet - Stefanets, V. P.; Sanina, N. A.; Shilov, G. V.; Dmitriev, A. I.; Zhidkov, M. V.; Aldoshin, S. M. (Russian chemical bulletin, 2024)
Two complex dysprosium( iii ) salts of composition Na[Dy(hfac) 4 ] (1) and Q[Dy(hfac) 4 ] 2 (2) , where hfac is the hexafluoroacetylacetonate anion and Q is 1,1′-dimethyl-4,4′-bipyridinium, were synthesized and studied by X-ray diffraction. An analysis of the X-ray diffraction data using the Shape program revealed noticeable distortions of two [DyO 8 ] coordination polyhedra of salt 2 anions; the Dy atoms are nonequivalent and have a biaugmented trigonal prismatic ( C 2v ) and triangular dodecahedral ( D 2d ) geometry. The experimental studies and the analysis of the magnetic properties of 2 showed that this compound exhibits a field-induced slow relaxation of magnetization, which is described by the Orbach mechanism ( U eff = 23.0 K, τ 0 = 2.68 · 10 −8 s).